Analysis of Health Benefits of Lenses: a Literature Review - Rahman, Ainur; Sumo, Maimon; Pu'adi, Pu'adi; Fadilah, Nur; Musyarrofah, Wilda; Mulyadi, Syifaul Aini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was conducted to determine the benefits of lenses on health; the aim of this article includes an in-depth understanding of the benefits of using lenses on eye health, identified through potential risks or health problems related to lens use, as well as investigations depending on the latest innovations or developments in lens technology that can improve eye well-being. In this descriptive research, the researcher uses a method in the form of a literature study that aims to observe, find out, assess, identify, analyze, and determine the topic of related research. The results of data analysis concluded that lenses have significant benefits for health, especially eye health. Lenses also help correct vision problems such as nearsightedness, farsightedness, and astigmatism. Lenses have significant health benefits, including protecting the eyes from dust and UV rays, aiding vision correction, reducing exposure to blue radiation, preventing dry eyes, and improving the quality of life for those with visual impairments. In various forms, lenses help maintain and improve eye health for overall comfort and well-being. Lenses can also help in particular situations, such as providing clarity of vision for athletes or physically active people and facilitating proper medical examinations and eye surgery procedures